The Skinner Box effect : sexual addiction and online pornography - Grundner, T. M. (Tom M.) (San Jose, CA : Writer's Club Press, 2000)
Among millions of people on the Internet there is a significant number who have become addicted to online pornography. Because of the "Skinner Box effect," pornography on the Internet is different and more virulent than its customary forms. Dr. Grundner provides a series of behavioral and spiritual techniques to help stop the problem and aid in recovery. Personal accounts of addcts are also presented.
Bottoming out -- Sexual addictions -- The Skinner Box effect -- Seeking help via the twelve step groups -- Breaking the box -- Higher powering -- They also serve who wait -- In our own words : the voices of addiction.
Keywords: Sex addiction; Sex addicts; Internet pornography